Anti-intermediate filament antibodies, antikeratin antibody, and antiperinuclear factor in rheumatoid arthritis and infectious mononucleosis. Issue 7 (July 1985) - Kataaha, P K; Mortazavi-Milani, S M; Russell, G; Holborow, E J
Abstract : Sera from patients with rheumatoid arthritis (RA), patients with infectious mononucleosis (IM), and blood donors were tested by indirect immunofluorescence for the presence of antikeratin antibody (AKA), antibody to cytoskeletal intermediate filaments of prekeratin or vimentin type (AIFA) and antiperinuclear factor (APF). In 81.9% of the RA sera and 92.5% of the IM sera AIFA of IgM class was found at titres up to and in some cases exceeding 1/160. In blood donors the incidence of AIFA was 26%, at titres not exceeding 1/20. AKA and APF, always of IgG class, were found in 54.2% and 73.6% of rheumatoid sera. A weak correlation was found in RA between the incidence of AIFA and APF. AKA was not present in either IM or blood donor sera, and APF was found in only 2.5% and 3.2% of IM or blood donors respectively.